Analisis Kebutuhan Investasi Sektor Unggulan di Kabupaten Rokan Hulu - Citra Sania Br. Ginting; Cepriadi; Novia Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Enhancing economic growth can be achieved by creating opportunities, realizing investments, and prioritizing key sector in regional development. This study aims to analyze the leading sectors in Rokan Hulu Regency and estimate the investment needs for each leading sector from 2025 to 2045. The study utilizes time series data from 2011 to 2023, including Gross Regional Domestic Product (GRDP) at constant prices by business field in Riau Province and Rokan Hulu Regency, as well as Gross Fixed Capital Formation (GFCF) at constant prices by expenditure. The analysis methods employed are Location Quotient (LQ), Dynamic Location Quotient (DLQ), Trend Analysis, and Incremental Capital Output Ratio (ICOR). The findings indicate that Rokan Hulu Regency has four leading sectors: agriculture, forestry, and fisheries; electricity and gas procurement; information and communication; and government administration, defense, and compulsory social security. These sectors have LQ and DLQ values greater than one, indicating that their contributions to the economy of Rokan Hulu Regency are higher than those of other sectors, both now and in the future. The total investment needs for Rokan Hulu's leading sectors from 2025 to 2045 are IDR 93,154,531 million for agriculture, forestry, and fisheries; IDR 10,223,150 million for electricity and gas procurement; IDR 24,457,547 million for information and communication; and IDR -48,632,099 million for government administration, defense, and compulsory social security.